Marketing Strategies in Peninsular Malaysia: Case Study of Gardenia Barkeries Sdn. Bhd. - Muhammad Fikri; Muhammad Aliff Aidil; Muhammad Amir; Nadiah Nadzhri; Shailendra Singh Sengar (AIBPM Publisher, 2022)
Â This study was conducted in order to investigate the marketing strategies of Gardenia Bakeries in Malaysia. Gardenia is a very well-known name by the majority of Malaysians. Therefore, the researchers choose this firm as the best topic for this case study. Gardenia has 4 production plants, 3 in Shah Alam and 1 in Puchong, Malaysia. Gardenia's marketing strategies make the company have a large market share in Malaysia despite having many competitors. This study was conducted using data collection which is gathered from journals and websites. Â The researchers also distributed a survey for this study with 80 respondents taking part in the online survey. The result shows that the customers are satisfied with the product's packaging and the price.Â